Analisis Praktik Jual Beli di Bawah Harga Pasar dalam Perspektif Maslahah Mursalah: Studi Kasus Tiktok Shop - Hirfa Diksagara Sinaga; Tetty Marlina Tarigan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
TikTok Shop is an e-commerce feature within the TikTok app that allows users to buy and sell products directly through videos, live streaming, and storefronts on user profiles. TikTok Shop often provides price subsidies so that products can be sold at lower prices than offline stores. The purpose of this study is to analyze the practice of buying and selling below market prices that is widespread on the TikTok Shop platform from the perspective of Maslahah Mursalah. By using empirical legal research, namely research that aims to examine law as a norm or rule that lives in society with the approach used conceptual approach and statute approach. The study shows that the practice of buying and selling below market prices carried out by large businesses and by platforms such as TikTok Shop has the potential to create price imbalances that cause small and medium enterprises to be unable to compete fairly. This contradicts the principle of prohibiting monopolistic practices and unfair business competition as regulated in Law Number 5 of 1999. It also contradicts the Maslahah Mursalah perspective in Islamic law, because it causes more mafsadah (damage) than temporary benefits.